Pengaruh Inflasi Dan Pertumbuhan Ekonomi Terhadap Kemiskinan Di Sumatera Baerat Tahun 2014-2021 - Afrianti, Rini (CV. ITTC INDONESIA, 2024)
The aim of this research is to analyze the partial and simultaneous influence of inflation and economic growth on poverty in West Sumatra. This research uses timeseries data with a time series from 2014-2023. The analysis method uses multiple linear regression analysis with the SPSS program. The research results show that the inflation variable (X1) is 1.311, a significant value of 0.031 > 0.05, which means that the inflation variable has a significant effect on poverty. economic growth (X2) has a significant value of 0.513 > 0.05, which means that the economic growth variable has no significant effect on the prominence of poverty. The calculated F value is 3.654, while the F table value is obtained through the F table (Dk=k-1, Df=n-k-1 so that Dk= 2-1=1 Df= 10-2-1= 7, so the F table value is 3 .14 ​​means that F count > F table (3.654 > 3.14) and a significant value of 0.000 < 0.05 results in a coefficient of determination of 0.511. This means that 51.1% of poverty is influenced by inflation and economic growth, while the remaining 48.9. % poverty is influenced by other variables not examined in this research.